In vitro Assessment of Chemical and Pre-biotic Properties of Carboxymethylated Polysaccharides From Passiflora edulis Peel, Xylan, and Citrus Pectin - Sun, Yongjin; Guan, Yuan; Khoo, Hock Eng; Li, Xia (Frontiers in Nutrition, 2021)
This study aimed to determine the carboxymethylation effect of crude water-soluble polysaccharides of Passiflora edulis peel (WPEP), xylan (XY), and citrus pectin (CP). Their chemical and prebiotic properties were also determined. The polysaccharides were carboxymethylated by reacting with chloroacetic acid and sodium hydroxide. The carboxymethylated and non-carboxymethylated polysaccharides were also used as prebiotics to study the growth pattern of selected intestinal microflora. These polysaccharides substituted the glucose solution in culture media for culturing Lactobacillus brevis GIM1.773, Lactobacillus plantarum GIM1.19, Lactobacillus delbrueckii subsp bulgaricus GIM1.155, and Streptococcus thermophilus GIM1.540. The results showed that the carboxymethylated polysaccharides c-XY, c-CP, and c-WPEP, had substitution degrees of 0.682, 0.437, and 0.439, respectively. The polysaccharides demonstrated resistance to digestion in the simulated human digestive models. The resistance to digestion was enhanced by carboxymethylation, especially the carboxymethylated CP and WPEP. The results also showed that the prebiotic activities of the polysaccharides increased after carboxymethylation. The c-XY had a better prebiotic effect than XY and the other carbohydrate samples. The findings suggested that carboxymethylated polysaccharides may be developed into novel prebiotics and nutraceuticals that could promote growth of the probiotic strains.